2011
DOI: 10.1111/j.1439-0264.2011.01112.x
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Relationship Between the Collecting System and the Intrarenal Arteries in the Rabbit: Contribution for an Experimental Model

Abstract: Intrarenal anatomy was studied in detail to evaluate how useful rabbits could be as a urologic model. Only one renal artery was observed, which was divided into dorsal and ventral branches in all cases. Three segmental arteries (cranial, mesorenal and caudal) was the most frequent branching pattern found in both the dorsal and ventral division. There was an important artery related to the ureteropelvic junction in both dorsal and ventral surfaces in all specimens. The cranial pole was supplied by both dorsal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 33 publications
3
21
0
Order By: Relevance
“…The caudal pole of the sheep kidney was irrigated by interlobar branches from the caudal segmental arteries of the dorsal and ventral primary branches of the renal artery in all cases. This branching pattern related to the caudal pole is similar to findings from dogs (Maques‐Sampaio et al, ) and rabbits (Shalgum et al, ), where the caudal pole is supplied by two caudal segmental arteries, one on the dorsal surface and another on the ventral surface. In pigs (84.62%) and humans (62%), the caudal pole is vascularized by single caudal and inferior segmental arteries, respectively, which divide into ventral (anterior) and dorsal (posterior) branches, sending interlobar branches on both ventral and dorsal surfaces of the caudal pole (Sampaio and Aragão, ; Pereira‐Sampaio et al, ).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The caudal pole of the sheep kidney was irrigated by interlobar branches from the caudal segmental arteries of the dorsal and ventral primary branches of the renal artery in all cases. This branching pattern related to the caudal pole is similar to findings from dogs (Maques‐Sampaio et al, ) and rabbits (Shalgum et al, ), where the caudal pole is supplied by two caudal segmental arteries, one on the dorsal surface and another on the ventral surface. In pigs (84.62%) and humans (62%), the caudal pole is vascularized by single caudal and inferior segmental arteries, respectively, which divide into ventral (anterior) and dorsal (posterior) branches, sending interlobar branches on both ventral and dorsal surfaces of the caudal pole (Sampaio and Aragão, ; Pereira‐Sampaio et al, ).…”
Section: Discussionsupporting
confidence: 88%
“…In sheep, a single renal artery was found in all cases, similar to pigs (Pereira‐Sampaio et al, ) and rabbits (Shalgum et al, ), but different from dogs where double (Maques‐Sampaio et al, ) or even triple renal arteries (Jain et al, ) have been reported. This finding is also different from human kidney, where multiple renal arteries are found in 27–30% of cases (Sampaio and Passos, ).…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations